Compact Synchrotron Light Sources - Weihreter E. Ernst (Series on Synchrotron Radiation Techniques and Applications Vol. 3)
This book covers a new niche in circular accelerator design, motivated by the promising industrial prospects of recent micromanufacturing methods — X-ray lithography, synchrotron radiation-based micromachining and microanalysis techniques. It describes the basic concepts and the essential challenges for the development of compact synchrotron radiation sources from an accelerator designer's point of view and gives an outline of the actual state of the art. The volume is intended as an introduction and as a reference for physicists, engineers and managers involved in this rapidly developing field.